Reimagining Learner Engagement Through Flipped Classrooms in the Post COVID-19 Era - Matiso, Nomasomi Hilda (Research in Social Sciences and Technology, 2024)
The post-COVID-19 era gave rise to the emergence of innovative teaching and learning strategies, which, among others, included flipped classrooms. This article sought to determine whether flipped classrooms are beneficial when online learning material is distributed prior the commencement of the class. Piaget’s (1986) Constructivist Learning Theory underpinned this inquiry. Constructivism is an approach to education that holds that people actively generate their own knowledge and that reality is shaped by the learner's experiences. The interpretive paradigm and a qualitative approach were utilized to collect information through semi-structured interviews with twelve conveniently selected grade 10 teachers. Using a case study design, the researcher could investigate the phenomenon in detail. Findings, which ensued from thematically analysed data, indicated that learners benefit most from pre-class activities as they offer increased participation opportunities as learners engage in discussions in their native languages. Thus, discussions and modelling tasks during in-class activities are learner-centred, with the development of paraphrasing skills, which promote good essay writing skills with minimum plagiarism effects. The author, therefore, recommends that Teachers require ongoing professional development in applying flipped classrooms using advanced learner-centred technological pedagogies, which promote maximum participation in the learning environment.